2021
DOI: 10.1007/s12237-021-01019-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability in Environmental Conditions Influences the Performance and Behavior of Juvenile Steelhead in a Coastal California Lagoon

Abstract: In California (USA), seasonal lagoons provide important oversummer rearing habitat for juvenile steelhead trout (anadromous Oncorhynchus mykiss). However, key water quality parameters such as temperature and dissolved oxygen concentration can periodically approach or exceed the physiological tolerances of steelhead during the protracted dry season. A field study employing distributed temperature sensing technology, water quality monitoring, habitat mapping, and mark-recapture sampling was conducted to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…On shorter time scales, Hadwen and Arthington (2006) reported that diversity and functioning of ICOLL communities in Australia were strongly influenced by entrance opening and closing regimes, with influence on diets of fishes and invertebrates. Mouth closure appears to reduce diversity relative to permanently open status (Pollard 1994b;Gray and Kennelly 2003), but there is conservation value to certain species associated with closed states (e.g., steelhead trout in Southern California) as well as temporally variable regimes of opening and closure (Watts and Johnson 2004;Hadwen and Arthington 2006;Bond et al 2022). For example, in the Carretas-Pereyra Lagoon (Mexico), which closes intermittently but is artificially opened for artisanal fishers (López-Vila et al 2021), there are half as many species reported as in a nearby permanently open lagoon (Gómez-González et al 2012).…”
Section: Low-inflow and Intermittently Closed Estuariesmentioning
confidence: 99%
“…On shorter time scales, Hadwen and Arthington (2006) reported that diversity and functioning of ICOLL communities in Australia were strongly influenced by entrance opening and closing regimes, with influence on diets of fishes and invertebrates. Mouth closure appears to reduce diversity relative to permanently open status (Pollard 1994b;Gray and Kennelly 2003), but there is conservation value to certain species associated with closed states (e.g., steelhead trout in Southern California) as well as temporally variable regimes of opening and closure (Watts and Johnson 2004;Hadwen and Arthington 2006;Bond et al 2022). For example, in the Carretas-Pereyra Lagoon (Mexico), which closes intermittently but is artificially opened for artisanal fishers (López-Vila et al 2021), there are half as many species reported as in a nearby permanently open lagoon (Gómez-González et al 2012).…”
Section: Low-inflow and Intermittently Closed Estuariesmentioning
confidence: 99%
“…Variation in migratory strategy may have substantial implications for the density and size structure of O. mykiss populations and, by extension, the management and ecology of freshwater ecosystems. Migration to the marine environment and/or highly productive estuarine rearing habitat typically allows individuals to achieve larger body sizes at maturation compared to those that remain in freshwater (Bond et al, 2022;Hayes et al, 2008;Kendall et al, 2015). Given the positive relationship between body size and fecundity in O. mykiss and other salmonids (Quinn, 2018), the reproductive potential of resident and migrant ecotypes can differ by orders or magnitude (Hayes et al, 2008(Hayes et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sawyer et al (in press) estimated that estuarine growth improved marine survival by 31-47% for juvenile coho salmon (O. kisutch) on the Central Coast of British Columbia and that growth was substantially higher in a year with warmer temperatures. On the other hand, observations from an estuary lagoon in California suggest that excessively high estuary temperatures can limit rearing habitat and drive diel movements for juvenile steelhead and coho salmon (Osterback et al, 2018;Bond et al, 2022). Thus, navigating mosaics of temperature in estuaries and the associated growth opportunities can have important consequences for juvenile salmon during estuary rearing and seaward migration.…”
Section: Introductionmentioning
confidence: 99%